The message of holiness : restoring God's masterpiece - Tidball, Derek (Downers Grove, Ill. : InterVarsity Press, 2010)
Derek Tidball surveys the Scriptures for a comprehensive biblical understanding of this elusive mandate from God to "be holy as I am holy." The triune God of glory, he contends, sets us on paths that lead us through encounters with God, ourselves, our enemies and our companions to our ultimate destination, where we discover that we have been reshaped by God into his own image. --from publisher description.
pt. 1. The foundation of holiness. God of the smoking mountain (Exodus 19:1-25) ; God in glory (Isaiah 6:1-13) ; God in Trinity (1 Peter 1:1-2, 13-21) -- pt. 2. Visions of holiness. Holiness as purity (Leviticus 11:1-47) ; Holiness as wisdom (Proverbs 2:1-22) ; Holiness as justice (Isaiah 58:1-14) -- pt. 3. The transformation of holiness. Holiness personified (Luke 1:35, 4:1, 34; 23:41) ; Holiness redefined (Matthew 5:20, 48; Mark 5:1-43; 7:1-23; Luke 14:1-4) ; Holiness orchestrated (John 17:6-19) -- pt. 4. The dimensions of holiness. Inner purity (Psalm 51) ; Personal holiness (1Thessalonians 4:1-12) ; Corporate holiness (1 Peter 2:4-10, Ephesians 4:17-5:20) ; Social holiness (Micah 6:1-8) -- pt. 5. Pathways to holiness. The Spirit of God (Galatians 5:13-6:10) ; The Word of God (2 Timothy 3:14-17) ; The discipline of God (Hebrews 12:1-17) ; Union with Christ (Romans 6:1-23) ; Conflict with the enemy (Ephesians 6:10-18) ; Separation from the world (2 Corinthians 6:14-7:1) -- pt. 6. The destination of holiness. To be like him (1 John 2:28-3:10) ; He will do it (1 Thessalonians 5:23-24) -- Study guide.
Includes bibliographical references (p. 13-19)
Keywords: Holiness -- Biblical teaching; Holiness -- Christianity